Harmony and divergence: Unraveling the influence of Surau in Minangkabau religious landscape - Alfurqan Alfurqan; M. Tamrin; Ahmad Taufik Hidayat; Wuri Syaputri (Cogent Arts & Humanities)
Surau appears to be the first institution and the main place of teaching where scholars educated the Minangkabau people on numerous concepts from the Middle East, resulting in the development of two distinct religious concepts. This article analyses the implications of these two differing perspectives in relation to religion, leading to a shift from a previously singular religious adherence to multiple practices. Based on primary-source material including treatises, letters and historical documents as well as employing comparative and oral-historical approaches, this research investigates the tension between tradition and reform in the Minangkabau societies. The study demonstrates that surau served not only as the site for the divergence of the ideologies, but also emerged as the space for mediation and reconciliation. These case studies contribute to our understanding of Islamic education by illustrating that the transformation of religion in Minangkabau was not the result of conflict, but rather of the rich and evolving situation in the region.